2017
DOI: 10.1080/10934529.2017.1293993
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine dioxide oxidation ofEscherichia coliin water – A study of the disinfection kinetics and mechanism

Abstract: This study investigated the kinetics and mechanism of chlorine dioxide (ClO) inactivation of a Gram-negative bacteria Escherichia coli (ATCC 35218) in oxidant demand free (ODF) water in detail as a function of disinfectant concentration (0.5-5.0 mg/L), water pH (6.5-8.5), temperature variations (4-37°C) and bacterial density (10-10 cfu/mL). The effects of ClO on bacterial cell morphology, outer membrane permeability, cytoplasmic membrane disruption and intracellular enzymatic activity were also studied to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 47 publications
2
37
3
Order By: Relevance
“…ClO 2 however was found to increase the permeability of the outer and cytoplasmic membranes leading to the leakage of membrane components such as 260 nm absorbing materials and inhibiting the activity of the intracellular enzyme β-Dgalactosidase (Ofori et al, 2017).…”
Section: Brief Communicationmentioning
confidence: 98%
See 1 more Smart Citation
“…ClO 2 however was found to increase the permeability of the outer and cytoplasmic membranes leading to the leakage of membrane components such as 260 nm absorbing materials and inhibiting the activity of the intracellular enzyme β-Dgalactosidase (Ofori et al, 2017).…”
Section: Brief Communicationmentioning
confidence: 98%
“…It has been reported that chlorine dioxide, a strong oxidant, can inhibit or destroy microorganisms (Ogata et al, 2008;Morino et al, 2009;Sanekata et al, 2010;Ma et al, 2017;Ofori et al, 2017). Sanekata et al, (2010) reported that chlorine dioxide at concentrations ranging from 1 to 100 ppm produced potent antiviral activity, inactivating >or= 99.9% of the viruses with a 15 sec treatment for sensitization.…”
mentioning
confidence: 99%
“…In general, disinfection of wastewater has been used since the beginning of the previous century and has subsequently reduced the risks of human exposure to pathogenic microorganisms. To date, the mostly used disinfection technique is chlorination (Solsona and Pearson, 1995;Carvajal et al, 2017;Gagnon et al, 2005;Li et al, 2017a;Lie et al, 2017b;Ofori et al, 2017). Chlorination is the process of adding the most widely applied chemical oxidant such as chlorine or hypochlorite to water in order to inactivate pathogens.…”
Section: Chlorinationmentioning
confidence: 99%
“…This is encouraging since dichlor and other stabilized chlorine products are routinely used in chlorinated recreation water venues throughout the United States. For Ofori et al (2017), the kinetics and mechanism of chlorine dioxide (ClO 2 ) inactivation of a Gram-negative bacteria Escherichia coli (ATCC 35218) in oxidant demand free (ODF) water is a function of disinfectant concentration (0.5-5.0 mg/L), water pH (6.5-8.5), temperature variations (4-37°C) and bacterial density (10 5 -10 7 cfu/mL). Increasing temperature and disinfectant concentration was found to be proportional to the rate of cell killing, but efficacy was found to be significantly subdued at 0.5 mg/L and less dependent on the bacterial density.…”
Section: Chlorinationmentioning
confidence: 99%
“…The pre-oxidant appears to have severely sensitized Planktothrix trichomes to the point where they become sensitive to shear stress (discussed in section 4.3). Cell damage of bacteria by chlorine is not fully understood and the underlying mechanisms are yet to be elucidated (Ofori et al, 2017). However, it could be proposed that the surface morphology of the cells/trichomes is altered in a way that weakens the trichome thus making it more susceptible to physical stressors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%